Co-culture of hematopoietic stem/progenitor cells with human osteblasts favours mono/macrophage differentiation at the expense of the erythroid lineage. - Simona Salati (Public Library of Science (PLoS), 2013)
Hematopoietic stem cells (HSCs) are located in the bone marrow in a specific microenvironment referred as the hematopoietic stem cell niche, where HSCs interact with a variety of stromal cells. Though several components of the stem cell niche have been identified, the regulatory mechanisms through which such components regulate the stem cell fate are still unknown. In order to address this issue, we investigated how osteoblasts (OBs) can affect the molecular and functional phenotype of Hematopoietic Stem/Progenitor Cells (HSPCs) and vice versa. For this purpose, human CD34+ cells were cultured in direct contact with primary human OBs. Our data showed that CD34+ cells cultured with OBs give rise to higher total cell numbers, produce more CFUs and maintain a higher percentage of CD34+CD38- cells compared to control culture. Moreover, clonogenic assay and long-term culture results showed that co-culture with OBs induces a strong increase in mono/macrophage precursors coupled to a decrease in the erythroid ones. Finally, gene expression profiling (GEP) allowed us to study which signalling pathways were activated in the hematopoietic cell fraction and in the stromal cell compartment after coculture. Such analysis allowed us to identify several cytokine-receptor networks, such as WNT pathway, and transcription factors, as TWIST1 and FOXC1, that could be activated by co-culture with OBs and could be responsible for the biological effects reported above. Altogether our results indicate that OBs are able to affect HPSCs on 2 different levels: on one side, they increase the immature progenitor pool in vitro, on the other side, they favor the expansion of the mono/macrophage precursors at the expense of the erythroid lineage.